Barriers to entry, market concentration, and wages in the Philippine manufacturing sector,1987 - Abenoja, Zeno Ronald R.; Lapid, Dennis D. (The Philippine Review of Business and Economics, 1991)
Market structure represents an important aspect of industries because a particular structure predetermines a set of assumptions in the analysis of markets. Market models used in policymaking should therefore reflect the actual level of competition in the industries. This characteristic becomes more important in the context of less developed economies, where perfectly competitive markets are more the exception than the rule. This paper examines the nature and the determinants of the market structure, as measured by concentration, in the Philippine manufacturing sector. It tries to verify the extent to which technological barriers to entry and foreign trade induce higher levels of concentration. It then extends the analysis to focus on the effects of concentration on the wage level in manufacturing industries. Cross-section data are used to test the hypothesis that higher concentration increases profits and thus leads to higher wages.